Legal Framework Governing Security and Fiduciary Collateral Repossession Service Providers in Financing Companies’ Asset Recovery Operations - Richard; Agus Sudrajat (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: This study aims to analyze the legal position of security and fiduciary collateral repossession service providers and to examine the legal framework governing fiduciary asset recovery practices in Indonesia following Constitutional Court Decision No. 18/PUU-XVII/2019. Research Design and Methodology: This study employed a normative juridical research design using statutory, conceptual, and case approaches through the analysis of fiduciary security regulations, the Indonesian Civil Code, judicial decisions, and relevant legal doctrines. Findings and Discussion: The findings reveal that repossession service providers occupy a derivative legal position based on a civil law mandate (lastgeving), whereby their authority depends entirely on the legality of creditors’ executorial rights. However, the absence of explicit regulations concerning their legal status, authority, accountability, and operational boundaries has created legal uncertainty, normative disharmony, and increased risks of criminalization and social conflict. The findings further demonstrate a substantial discrepancy between normative expectations and practical implementation in fiduciary asset recovery practices. This study proposes an integrated fiduciary asset recovery governance model that combines explicit legal recognition, standardized operating procedures, institutional supervision, and human rights safeguards. Implications: These findings provide important implications for policymakers and financing institutions by promoting a more transparent, accountable, and sustainable fiduciary asset recovery system, while also offering a foundation for future socio-legal and comparative studies on fiduciary security governance.